Intravenous Laser Therapy in Patients With Acute Kidney Injury: A Randomized Clinical Trial: Intravenous Laser Therapy in Patients With AKI - Razzaghi, Mohammad Reza; Ghanei, Esmat; Malekian, Sheida; Mazloomfard , Mohammad Mohsen (Journal of Lasers in Medical Sciences, 2021)
Introduction: Although intravascular laser irradiation of blood (ILIB) is deemed an innocuous and a useful technique for laser therapy, particularly when systemic effects are required, no study, to our knowledge, has been conducted on the effectiveness and innocuousness of ILIB in treating acute kidney injury (AKI). Objective: This study aimed to assess the feasibility and outcomes of ILIB in the management of patients with AKI and comparing them with the Sham-laser group. Materials and Methods: Twenty-six patients with intra-renal AKI (24-95 years old) at Tajrish Hospitals were evaluated for enrollment eligibility in this clinical trial study. This study was conducted at the nephrology department of Shahid Beheshti University of Medical Science, Tehran, Iran, between 2018 and 2019. Based on the treatment method, the patients’ assignment to two groups (ILIB or Sham-laser) was randomly done. Demographic characteristics need for dialysis, hemoglobin and serum biochemistry changes, serum, and urine neutrophil gelatinase-associated lipocalin (NGAL) changes, laser complications, and the hospitalization period were recorded. Results: In terms of the baseline characteristics and biochemistry serum level, no differences were seen between the two groups. All post-treatment parameters, except the hemoglobin value, significantly improved in both groups. Urine NGAL and serum NGAL show decline from the baseline in both groups; however, the reduction slope of these parameters occurred faster in the laser group in a statistically significant manner. Conclusion: A decline in NGAL levels in the laser group during the treatment may suggest that the ILIB can help patients with AKI recover better. DOI:10.34172/jlms.2021.49.